2019
DOI: 10.3390/cells8040323
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Use of Metformin, Dipyridamole, N-Acetylcysteine and Statins as Adjunctive Therapy for Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune condition that can potentially affect every single organ during the course of the disease, leading to increased morbidity and mortality, and reduced health-related quality of life. While curative treatment is currently non-existent for SLE, therapeutic agents such as glucocorticoids, mycophenolate, azathioprine, cyclosporine, cyclophosphamide and various biologics are the mainstay of treatment based on their immunomodulatory and immunosupp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 96 publications
0
23
0
2
Order By: Relevance
“…Dipyridamole is an FDA-approved nonspecific PDE inhibitor used for thrombosis and was discovered to inhibit NET formation ( Ali et al, 2019 ). Dipyridamole acts by increasing intracellular cAMP levels and blocking adenosine reuptake in cells, thereby leading to its antiplatelet and vasodilatory effects ( Tan et al, 2019 ). In a trial including 31 COVID-19 patients, dipyridamole showed improvement in severe cases with significantly reduced D-dimer levels ( Liu et al, 2020 ).…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%
“…Dipyridamole is an FDA-approved nonspecific PDE inhibitor used for thrombosis and was discovered to inhibit NET formation ( Ali et al, 2019 ). Dipyridamole acts by increasing intracellular cAMP levels and blocking adenosine reuptake in cells, thereby leading to its antiplatelet and vasodilatory effects ( Tan et al, 2019 ). In a trial including 31 COVID-19 patients, dipyridamole showed improvement in severe cases with significantly reduced D-dimer levels ( Liu et al, 2020 ).…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%
“…In addition, some studies have investigated hydroxychloroquine in association with metformin in diabetic patients to achieve a better control of type-2 diabetes conditions [10]. Conversely, metformin was studied as an adjunctive therapy for systemic lupus erythematous, a condition for which hydroxychloroquine is routinely administered [11]. In fact, our study was prompted by the paper from Rajeshkumar's group [5] showing a higher mortality ratio (30-40%) in mice treated with hydroxychloroquine + metformin in comparison with the control group receiving metformin alone.…”
Section: Discussionmentioning
confidence: 99%
“…Values were expressed as mean ± standard deviation (SD) unless otherwise specified. Continuous and discrete variables between the SLE and HC groups were compared by using Mann-Whitney U test and χ 2 test, respectively. Correlations between IFC of each protein and demographic and clinical parameters were explored by bivariate correlation analyses.…”
Section: Methodsmentioning
confidence: 99%